2010
DOI: 10.1007/s11282-010-0039-4
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional observations of the incisive canal and the surrounding bone using cone-beam computed tomography

Abstract: Objectives The shape of the anterior region of the maxilla is critical when planning implant treatment. The purpose of the present study was to assess the typical morphology of the incisive canal and surrounding bone. Methods In total, 70 maxillae of Japanese dry skulls were used after being divided into dentate and edentulous groups. Cone-beam computed tomography (CBCT) images of the maxilla were acquired by using standardized methods. Using the anterior nasal spine as a reference point, the change in positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
50
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 17 publications
(19 reference statements)
13
50
4
1
Order By: Relevance
“…4,5) The mean antero-posterior angulation at the inferior level was 75.3 degrees in IIIC, and the value was close to that of adults (mean: 74.3 degrees) in a previous study. 4) The mean difference of angulation between the inferior and middle levels was lower in IIA and IIC, and it was understood that the maxillary incisive canal was straight from the inferior level to nasal floor. Significant differences with different of angulations were noted between IIC and after IIIA.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…4,5) The mean antero-posterior angulation at the inferior level was 75.3 degrees in IIIC, and the value was close to that of adults (mean: 74.3 degrees) in a previous study. 4) The mean difference of angulation between the inferior and middle levels was lower in IIA and IIC, and it was understood that the maxillary incisive canal was straight from the inferior level to nasal floor. Significant differences with different of angulations were noted between IIC and after IIIA.…”
Section: Discussionsupporting
confidence: 83%
“…It was suggested that the increase of the antero-posterior axis continued in stages after IIIC. Also, Asaumi et al 4) reported that mean antero-posterior and lateral axes in adults with dentate were 3.8 mm and 3.7 mm at the inferior level, and 2.8 mm and 3.3 mm, respectively. The ratio of lateral axis to antero-posterior axis simply calculated was 0.97 at the inferior level, and 1.18 at the middle level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, more than 60% of our subject pool had an incisive canal width larger than the interroot distance, and individual variations of canal dimension, especially enlargement and asymmetry of the canal morphology, are frequently reported with 3D evaluation. 20,21,30,31 Anatomical features of the incisive canal have been studied in connection with rehabilitation of the maxillary anterior region [18][19][20][21][22][23][24] and the placement of orthodontic mini-implants. 30,[32][33][34] However, the consequences or the possibilities of incisor roots being in contact with the incisive canal following tooth movement are poorly documented in the orthodontic literature.…”
Section: Discussionmentioning
confidence: 99%
“…The most common surgical procedures in this region (also known as the premaxillary zone) include the extraction of impacted or supernumerary teeth, implant placement, endodontic treatment, periodontal surgery, the elimination of cysts, and orthognathic surgery …”
Section: Introductionmentioning
confidence: 99%